2020
DOI: 10.1111/ejh.13398
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of porcine ALG compared to rabbit ATG as first‐line treatment for children with acquired aplastic anemia

Abstract: Objective To assess the outcomes of children with acquired aplastic anemia (AA) treated in China with first‐line porcine anti‐lymphocyte immunoglobulin (p‐ALG)/rabbit anti‐thymocyte immunoglobulin (r‐ATG) combined with cyclosporine A (CSA). Methods We performed a single‐center, non‐randomized, retrospective cohort study to assess the outcomes of 189 children with AA treated in China with first‐line p‐ALG/r‐ATG combined with CSA between 2014 and 2018. Results No significant differences were observed in the over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…After 6 months of IST, CsA was continually administered, and the patients were closely followed up with; each family gave full consent, or there were no other options available. With this CsA administration management, the results of the present study were partially consistent with Zhu’s; 33 however, there were no data with porcine anti-LY immunoglobulin included in the present study. Together, the stronger and longer immunosuppressive rATG effect, lower trough level, and prolonged use of CsA within the follow-up period might have contributed to a higher response rate, especially in patients with SAA and VSAA who did not have MSDs.…”
Section: Discussionsupporting
confidence: 87%
“…After 6 months of IST, CsA was continually administered, and the patients were closely followed up with; each family gave full consent, or there were no other options available. With this CsA administration management, the results of the present study were partially consistent with Zhu’s; 33 however, there were no data with porcine anti-LY immunoglobulin included in the present study. Together, the stronger and longer immunosuppressive rATG effect, lower trough level, and prolonged use of CsA within the follow-up period might have contributed to a higher response rate, especially in patients with SAA and VSAA who did not have MSDs.…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, in our study, the incidence of CMV viremia and EBV viremia was significantly lower in the P-ALG group than the R-ATG group (46.4% vs 71.4%, P = 0.022 and 3.6% vs 25.4%, P = 0.014). Previous studies of ATG/ALG in IST indicated more clearance of peripheral blood lymphocytes by R-ATG than by P-ALG [ 9 , 10 , 25 ]. Patients in R-ATG group had a significantly lower minimum number of lymphocytes than the P-ALG group and remained significantly lower after 1, 3 and 6 months of treatment initiation and recovered to equivalent levels after 12 months [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, horse ATG is not available in China, while a new porcine anti-lymphocyte globulin (P-ALG) is available. Several studies have compared the efficacy and safety of R-ATG and P-ALG in IST and suggested that P-ALG was similar to or even better than R-ATG [ 9 11 ]. In addition, P-ALG containing conditioning regime before HSCT in the setting of MSD-HSCT and MUD-HSCT have also demonstrated good efficacy and tolerance [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The optimal balance between treatment benefits (immunological and kidney protective) and risks (infections) of the typical lymphocyte-depleting antibody rATG still remains to be properly elucidated. pALG has been already used in the hematology and transplantation fields ( 20 , 23 ), and offers an appropriate option to build an individualized induction therapy based on relevant immunological characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike rATG which is made in rabbits, pALG origins are from a genetically closer species to humans and therefore improved antigenic similarity, which may result in weaker cytolytic capacity on human lymphocytes than rATG ( 19 ). pALG has been successfully used as first-line treatment in acquired severe aplastic anemia ( 20 22 ). It has also been employed for other hematological indications such as graft versus host disease prophylaxis ( 23 ).…”
Section: Introductionmentioning
confidence: 99%